Alteration of volatile compounds profile of brewers? spent grain by bath-ultrasonication and its combination with conventional water-bath and autoclave treatment - Naibaho Joncer; Pudło Anna; Korzeniowska Małgorzata; Lu Yuyun; Yang Baoru (ELSEVIER, 2022)
The study aimed to investigate the capability of bath-ultrasonication and its combination with conventional water-bath and autoclave treatment in modifying the volatile composition of brewers’ spent grain (BSG). It was hypothesized that the treatments modified the volatile composition of BSG due to the sonochemical modification. The results demonstrated that the treatments intensified the desirable odor and removed the undesirable one which might allow the possibility of masking and renewing the odor perception of BSG. Besides the influence on odor perception related compounds, it is worth to highlight that the treatments eliminated herbicidal compounds such as (E,E)-2,4-heptadienal and (E)-2-hexenal which might be present from herbicidal treatment. Combination of bath-ultrasonication with autoclave treatment modified the volatile aldehydes while its combination with conventional water-bath generated the same profile as it was in untreated BSG. Time elevation on bath-ultrasonication had no significant impact on the amount of ketones and alkanes, while the fluctuation occurred as an impact of thermal exposures. Moreover, the treatment reduced the amount of alcohol and increased the fatty acids. In conclusion, bath-ultrasonication and its combination with thermal exposure modified the volatile compositions of BSG.